Unravelling the mechanism of water sensing by the Mg2+ dihydroxy-terephthalate MOF (AEMOF-1′). Issue 2 (4th October 2019) - Papazoi, Eleutheria; Douvali, Antigoni; Diamantis, Stavros A.; Papaefstathiou, Giannis S.; Eliseeva, Svetlana V.; Petoud, Stéphane; Hatzidimitriou, Antonios G.; Lazarides, Theodore; Manos, Manolis J.
Abstract : The amorphous compound [Mg(H2 dhtp)(H2 O)2 ] 1′ was shown to be a highly efficient and reusable luminescent sensor for the detection of water in THF, due to its transformation to the strongly emissive complex [Mg(H2 dhtp)(H2 O)5 ]·H2 O 1 . Abstract : In this contribution we build upon our previous work on the MOF [Mg(H2 dhtp)(H2 O)2 ]·DMAc (AEMOF-1 ·DMAc) and its activated dry version AEMOF-1 ′ which has been shown to exhibit excellent luminescence sensing properties towards water in organic solvents. We demonstrate through combined structural and photophysical studies that the observed changes in the fluorescence properties of AEMOF-1 ′ upon hydration arise from a structural transformation to the mononuclear complex [Mg(H2 dhtp)(H2 O)5 ]·H2 O (H4 dhtp = 2, 5-dihydroxyterepthalic acid) (1 ). In the latter complex, excited state intramolecular proton transfer (ESIPT) is strongly favoured thereby leading to enhanced and red shifted emission in comparison to AEMOF-1 ·DMAc. Powder X-ray diffraction measurements confirmed that complex 1 is identical to the hydrated form of AEMOF-1 ·DMAc. As in the case of AEMOF-1 ′, the dry form of complex 1 (1′ ) is also an effective sensor for the determination of traces of water in tetrahydrofuran (THF). This work demonstrates that the same chromophore may exhibit very different emission properties when it exists in different chemical environments and that these transformations may be controlled and utilized in water sensing applications.